'Cruising toward nuclear danger': Canadian anti-nuclear activism, Pierre Trudeau's peace mission, and the transatlantic partnership. Issue 1 (2nd January 2018) - Colbourn, Susan
Abstract: In March 1982, news broke that the US Air Force planned to test cruise missiles in Canada. The issue brought the Euromissiles Crisis home to Canada, as Canadians took to the streets in record numbers to oppose the tests. Anti-nuclear activists linked their 'refuse the cruise' protests to anti-nuclear demonstrations taking place across the West. Prime Minister Pierre Trudeau too saw testing in a transatlantic context, insisting they were part of Canada's NATO obligations. Neither European nor American, the Canadians had an unusual place in NATO. Often, this translated to being completely ignored: transatlantic issues, including the decade-long Euromissiles Crisis, tended to be seen as US–Western European issues. This article considers the ways in which the Euromissiles Crisis came home to Canada and situates Canada in a broader transatlantic landscape. The Euromissiles Crisis framed Canadian debates over cruise missile testing, encouraging activists and politicians to think about how the threat of nuclear war could be reduced.